Applicability of Exercise and Education Programmes for Knee Osteoarthritis Management to Switzerland - Ettlin, Lea; Rausch Osthoff, Anne-Kathrin; Nast, Irina; Niedermann, Karin (Frontiers in Health Services, 2021)
Objectives: The aim of this study was to assess the applicability of six OARSI (Osteoarthritis Research Society International) approved exercise and education programmes for the conservative management of knee osteoarthritis to the Swiss health care system. Methods: The RE-AIM framework was used in this cross-sectional survey study to analyse the characteristics of the six exercise and education programmes. A survey was developed based on the RE-AIM dimensions, “Reach, Effectiveness, Adoption, Implementation and Maintenance”, for rating the applicability of the programmes (on a scale of 1 = “least applicable” to 10 = “most applicable”). Programme scores of ≥7 indicated applicability to the Swiss health care system. Nine selected physiotherapy experts for knee OA management in Switzerland were invited for the rating. Results: The six programmes were rated by six of the nine invited research experts with mean scores of between 5.9 and 9.45. Four programmes scored 7 or more. These four programmes all included supervised exercise sessions and education with the goal that the participants understand the diagnosis and the management of OA. The two lower rated programmes focused on exercise counselling or weight reduction. Conclusion: The programme with the highest scores consists of exercise and education and scored higher than 7 in all RE-AIM dimensions. Therefore, this programme is most applicable to the Swiss health care system as only few adaptations would be needed for its successful implementation.